2011
DOI: 10.1007/s00167-011-1616-8
|View full text |Cite
|
Sign up to set email alerts
|

Navigated opening wedge high tibial osteotomy improves intraoperative correction angle compared with conventional method

Abstract: III.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
106
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(113 citation statements)
references
References 34 publications
6
106
0
1
Order By: Relevance
“…In our study, the navigation system did not improve the precision in the correction of the mechanical axis (p=0.733), as previously shown in the literature; Lützner et al [15], in their experiment with 19 cadavers, obtained better correction of the line of load with navigation, and Akamatsu et al [21] also concluded that navigation can reduce the risk of hypocorrection, allowing better intra-operative control of the mechanical axis and tibial slope as compared with the traditional technique. In our clinical study, despite the lack of significant differences between groups regarding the mean mechanical axis, we did observe that the dispersion was higher in the control group; the coefficient of variation of the mechanical axis was 58 % around the mean for the navigation system and 97 % around the mean for the control group, operated with the traditional open wedge HTO.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In our study, the navigation system did not improve the precision in the correction of the mechanical axis (p=0.733), as previously shown in the literature; Lützner et al [15], in their experiment with 19 cadavers, obtained better correction of the line of load with navigation, and Akamatsu et al [21] also concluded that navigation can reduce the risk of hypocorrection, allowing better intra-operative control of the mechanical axis and tibial slope as compared with the traditional technique. In our clinical study, despite the lack of significant differences between groups regarding the mean mechanical axis, we did observe that the dispersion was higher in the control group; the coefficient of variation of the mechanical axis was 58 % around the mean for the navigation system and 97 % around the mean for the control group, operated with the traditional open wedge HTO.…”
Section: Discussionsupporting
confidence: 87%
“…The mechanical axis was better controlled, but the tibial slope and the clinical evaluation were different. In the study by the Kim group [16], the clinical outcome was better with the navigation system, but not the control of the tibial slope; on the other hand, Akamatsu et al [21] obtained better slope control but this was not reflected in improvement of the clinical aspects. In both studies the mean follow-up time was 12 months, like in ours, and follow-up is indeed one of the limitations of our study.…”
Section: Discussionmentioning
confidence: 93%
“…5,16) Our hypothesis was that the amount of SPA performed by elderly patients might improve after OWHTO. However, the improvement ratio of SPA was 19.6% (<20%).…”
Section: Discussionmentioning
confidence: 99%
“…1,2) By changing the axis of the lower limb using an extra-articular approach, OWHTO preserves the native articular surface and decreases the excess stress in the medial compartment of the knee. [3][4][5] After OWHTO, patients generally have no limits on their activities of daily living. Excellent clinical results of OWHTO have been reported.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation